Kinerja Rasio Keuangan Perbankan Islam Dan Konvensional: Studi Komparatif - Amrizal Amrizal (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2013)
The article focuses to analyze finance ratio consist of Return on Assets (ROA), Return on Equity (ROE), Net Interest Margin (NIM) Capital Adequacy Ratio (CAR) except Earnings before Interest Tax (EBIT). The research is conducted to three conventional banking (BNI 46, Mandiri and BRI) and three syariah banking (Bank Muamalat Indonesia, Bank Mega Syaria and Bank Syariah Mandiri) for annual report periods 2007 to 2011. The result shows, the average increase EBIT to conventional banking groups during period 2007 to 2011 are 1.91% while the average EBIT to syariah banking groups are 1.53%. The average of ROA to conventional banking groups are 3.01% while the average ROA to syariah banking groups are 1.99%. The average of ROE to conventional banking groups is 24.19% while the average of ROE to syariah banking groups is 33.31%. The average of NIM to conventional banking groups during period 2007 to 2011 are 7.08% while the average of NIM to syariah banking groups during period 2007 to 2011 are 8.14%. The average of CAR to conventional banking groups is 15.63%, while the average of CAR to syariah banking groups during the period are 12.19%.